Impact of switching to a heat-not-burn tobacco product on CYP1A2 activity. (2020) - van der Plas, Angela; Pouly, Sandrine; Blanc, Nicolas; Haziza, Christelle; de La Bourdonnaye, Guillaume; Titz, Bjorn; Hoeng, Julia; Ivanov, Nikolai V.; Taranu, Brindusa; Heremans, Annie
Abstract: Background: Cigarette smoking induces cytochrome P450 1A2 (CYP1A2) expression and activity, while smoking cessation normalizes the levels of this enzyme. The aim of this publication is to summarize the data on CYP1A2 gene expression and activity in preclinical and clinical studies on the Tobacco Heating System (THS), currently marketed as IQOS® with HEETs®, and to summarize the potential effects on CYP1A2 to be expected upon switching to reduced-risk products (RRPs). Methods: We summarized PMI's preclinical and clinical data on the effects of switching from cigarette smoking to THS. Results: Data from four preclinical mouse and rat studies showed that, upon either cessation of cigarette smoke exposure or switching to THS exposure, the upregulation of CYP1A2 observed with exposure to cigarette smoke reverted close to fresh-air levels. Data from four clinical studies yielded similar results on CYP1A2 activity within a time frame of five days. Furthermore, the effects of switching to THS were similar to those seen after smoking cessation. Conclusions: Because smoking cessation and switching to either electronic cigarettes or THS seem to have similar effects on CYP1A2 activity, the same measures taken for patients treated with narrow therapeutic index drugs that are metabolized by CYP1A2 and who quit smoking should be recommended for those switching to RRPs.